2020
DOI: 10.1039/d0gc02286a
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for producing bio-based anode materials for lithium-ion batteries

Abstract: A simple, scalable, and relatively green alternative method for producing graphite anode material for lithium-ion batteries is developed and demonstrated. A low-cost, earth abundant iron powder is used to catalyze...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 30 publications
2
46
1
Order By: Relevance
“…6 ) and intensity ratios (Supplementary Fig. 7 ) of the top-surface material showed a striking resemblance with materials obtained by treating organic precursors at very high temperatures, around 2500–3000 °C 11 , 31 , 51 . This is remarkable, since such temperature values could hardly be reached by our laser system even with a power up to 13 W. We note here that the bright spark arising from the lasing of ink-coated samples (Supplementary Movie 1 , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…6 ) and intensity ratios (Supplementary Fig. 7 ) of the top-surface material showed a striking resemblance with materials obtained by treating organic precursors at very high temperatures, around 2500–3000 °C 11 , 31 , 51 . This is remarkable, since such temperature values could hardly be reached by our laser system even with a power up to 13 W. We note here that the bright spark arising from the lasing of ink-coated samples (Supplementary Movie 1 , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 71%
“…It is known that certain transition metal cations, such as iron, can have a beneficial effect on the hydrothermal carbonization and pyrolytic graphitization of organic materials, including wood, thanks to thermo-catalytic effects 13 , 35 , 51 , 53 57 . Since our ink contains iron, it is reasonable to hypothesize that thermo-catalytic processes could have promoted efficient laser-induced graphitization already at temperatures between 1200 °C and 1600 °C, well within the expected reach of our lasing parameters 13 , 51 . For this reason, we call our approach iron-catalyzed laser-induced graphitization (IC-LIG).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary to the previously described works which mainly focused on obtaining hard (amorphous) carbons from wood, Park and coworkers developed a method to produce highly crystalline graphitic carbon from bio‐based precursors in a simple way. [ 124 ] They studied the catalytic graphitization of glucose, cellulose, lignin, hardwood, and softwood by dry mixing the precursor with iron powder, heating up to 1200 °C and acid washing with concentrated HCl (37% w/w). The characterization revealed that the graphite produced from softwood exhibited the highest degree of graphite purity, which was further characterized in a half‐cell versus lithium, showing high C‐rate capability up to 2C, and high reversibility over 100 cycles at 0.5C.…”
Section: Wood As Active Materialsmentioning
confidence: 99%
“…5−9 In particular, biochar produced from lignin feedstocks shows higher biochar yields and electrical conductivity than that produced from other biomass precursors. 6,10 Furthermore, lignin is a well-known waste byproduct of the papermaking industry and biorefinery processes; upcycling waste lignin into a valuable product can improve the sustainability of these industries and advance the circular economy. 11 Biochar has previously been studied as an alternative active material to graphite in the anode of LIBs.…”
Section: ■ Introductionmentioning
confidence: 99%